COMPARISON OF PATIENT SATISFACTION BETWEEN KRIS-JKN AND NON-KRIS-JKN IN YOGYAKARTA PUBLIC HOSPITAL - Faizqinthar Bima Nugraha; Arif Sabta Aji; Arida Oetami; Nurul Ima Alfiah (Jurnal Manajemen Kesehatan Indonesia, 2026)
Since January 2024, the public hospital (RSUD) in Yogyakarta City has been implementing a KRIS-JKN trial using 12 standard dimensions to improve the quality of inpatient services. This study aimed to determine the difference in inpatient satisfaction between KRIS-JKN and non-KRIS-JKN patients at Yogyakarta City Hospital across five service dimensions: tangible, reliability, responsiveness, assurance, and empathy. The study was conducted from December 2024 to January 2025 using a cross-sectional design with purposive sampling, involving 108 inpatients. A validated satisfaction questionnaire was used, and data were analyzed using t-test and Mann-Whitney test with SPSS version 23.0. The results showed that most respondents were female (51.9%, p=0.425), with no significant difference in satisfaction based on demographic characteristics. However, non-KRIS-JKN patients reported higher satisfaction (139.04±3.826) than KRIS-JKN patients (134.00±3.251). Significant differences were found in all dimensions: tangible (p=0.001), reliability (p=0.002), responsiveness (p=0.001), assurance (p=0.001), and empathy (p=0.001), with non-KRIS-JKN patients showing consistently higher scores. These findings indicate that KRIS-JKN implementation still needs improvement in several aspects. Before full implementation, hospitals should prioritize better lighting, accessible bathrooms, and regular monitoring of room temperature and humidity through ventilation maintenance using thermometers and hygrometers to ensure patient comfort and quality care. Keywords: KRIS-JKN, Patient Satisfaction, Hospitalisation, Yogyakarta.